Efficacy and safety of peppermint extract (Mentha Piperita), probiotics, and the co-administration of peppermint plus probiotics in preventing ascites syndrome: A clinical animal study on male broilers - Haghighat-Jahromi, Marjan; Talebi , Ebrahim; Naemi , Mehdi; Rakhshan, Vahid (Journal of Poultry Sciences and Avian Diseases, 2025)
Ascites syndrome is a serious and common condition in broilers. Therefore, we aimed to assess the preventive efficacy and safety of peppermint extract, probiotics, and their combination on ascitic broilers versus normal ones. In this clinical animal study, 168 male one-day-old broilers of the Ross 308 strain with similar weights were bred and vaccinated until day 20. On day 21, they were weighed and randomized into 8 groups of 21 broilers each: the negative control (no ascites and no treatments), peppermint extract administration, probiotics consumption, peppermint extract and probiotics co-administration, induced ascites (the positive control), induced ascites + peppermint extract, induced ascites + probiotics, and induced ascites + the co-administration of peppermint and probiotics. Until day 42, medications (levothyroxine, peppermint extract, or probiotics) were applied. On day 42, 10 broilers were randomly selected from each group (n=80), weighed, and blood-sampled. Data were analyzed (α=0.05). Peppermint extract and probiotic administration alone were relatively safe. However, the combination of peppermint extract and probiotics might have deleterious effects in healthy broilers in terms of most of the parameters (AST/ALT/ALP/T3/T4/glucose/ cholesterol/triglycerides/total protein/RBC, P<0.05). In ascitic broilers, peppermint extract almost always had a positive therapeutic effect, either improving the parameters of the control levels or improving some levels between the control and diseased (all parameters except ALP and RBC). Probiotics had several such positive effects as well (in the case of AST, ALT, T3, T4, glucose, BUN, uric acid, total protein, albumin, globulin, hematocrit, weight gain), although mostly not as strong as those of peppermint. The co-administration of peppermint extract and probiotics caused slight improvements only for 2 parameters (uric acid and ALT) in ascitic broilers. Peppermint ‎extract followed by probiotics (but not their combination) were safe and effective in preventing the ascites syndrome. The use of their combination should be avoided.